Enhancing Social Participation in Rural Communities: Analyzing International Experiences and Practical Strategies for Afghanistan - Yar, Fayaz Gul Mazloum; Noori, Ahmad Sabir; Zazai, Janat Gul (Syntax Literate, 2025)
Social participation is a cornerstone of sustainable rural development, particularly in fragile states like Afghanistan. This study investigates the challenges and opportunities of fostering social participation in rural Afghan communities by analyzing successful international models and proposing practical strategies tailored to the local context. Drawing from global experiences in countries such as India, Bangladesh, and South Korea, the research highlights key factors such as policy frameworks, decentralized governance, inclusion of marginalized groups, and capacity building. The study employs a qualitative methodology, integrating secondary data analysis and expert consultations to identify actionable recommendations. Findings reveal that while Afghanistan’s traditional governance structures, like shuras and jirgas, provide a foundation for participation, significant barriers such as gender inequality, limited decentralization, and inadequate resources persist. The proposed strategies emphasize integrating traditional and modern participatory approaches, leveraging digital tools, and enhancing collaboration between government institutions and NGOs. This research contributes to the broader discourse on participatory rural development, offering insights into building resilient, inclusive communities in fragile contexts.